Un pueblo frente al espejo : nueva narrativa de la Semana Santa guatemalteca. - Santa Cruz, Fernando Barrillas; Salinas, Luis Méndez; Chaulón Vélez, Mauricio José (Nueva narrativa de la Semana Santa guatemalteca ;, 2021)
.